Circular dichroism in non-chiral metal halide perovskites. Issue 35 (21st August 2020) - Sercel, Peter C.; Vardeny, Zeev Valy; Efros, Alexander L.
Abstract : Non-chiral orthorhombic perovskite nanostructures can exhibit chiro-optic effects under off-normal illumination due to the Rashba effect. Abstract : We demonstrate theoretically that non-chiral perovskite layers can exhibit circular dichroism (CD) in the absence of a magnetic field and without chiral activation by chiral molecules. The effect is shown to be due to splitting of helical excitonic states which can form in structures of orthorhombic or lower symmetry that exhibit Rashba spin effects. The selective coupling of these helical exciton states to helical light is shown to give rise to circular dichroism. Polarization dependent absorption is shown to occur due to the combined effect of Rashba splitting, in-plane symmetry breaking, and the effect of the exciton momentum on its fine structure, which takes the form of Zeeman splitting in an effective magnetic field. This phenomenon, which can be considered as a manifestation of extrinsic chirality, results in significant CD with an anisotropy factor of up to 30% in orthorhombic perovskite layers under off-normal, top illumination conditions, raising the possibility of its observation in non-chiral perovskite structures.